2017
DOI: 10.1103/physrevlett.118.267002
|View full text |Cite
|
Sign up to set email alerts
|

Topological Quantum Liquids with Long-Range Couplings

Abstract: Very few topological systems with long-range couplings have been considered so far due to our lack of analytic approaches. Here we extend the Kitaev chain, a 1D quantum liquid, to infinite-range couplings and study its topological properties. We demonstrate that, even though topological phases are intimately linked to the notion of locality, the infinite-range couplings give rise to topological zero and nonzero energy Majorana end modes depending on the boundary conditions of the system. We show that the analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…This implies that the entanglement entropy may violate the area law while the system is non critical. This happens in the so-called Long-Range Kitaev chain [8,9], which has been the object of an intense study in the last years [10][11][12][13][14]. Apart from the theoretical interest, as a model to analyse the role of conformal symmetry in critical points, there has been recently a spectacular development of experimental devices where these long range interactions can be simulated [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the entanglement entropy may violate the area law while the system is non critical. This happens in the so-called Long-Range Kitaev chain [8,9], which has been the object of an intense study in the last years [10][11][12][13][14]. Apart from the theoretical interest, as a model to analyse the role of conformal symmetry in critical points, there has been recently a spectacular development of experimental devices where these long range interactions can be simulated [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Even more interestingly, very recent works [26,28,29,[35][36][37][38][39][40][41][42][43] have suggested that LR systems can host new phases at sufficiently small values of the decay exponents α for the Hamiltonian terms. These phases often manifest interesting features not owned by the SR ones, including continuous quantum phase transitions without mass gap closure, violation of the area-law for the von Neumann entropy and of the Mermin-Wagner theorem, emergence of massive edge states.…”
Section: Introductionmentioning
confidence: 99%
“…Generalization to long-range Kitaev chain and higher dimensions.-We further give an example of a Kitaev chain with long-range pairing [54][55][56][57]:…”
mentioning
confidence: 99%